Carbon dioxide-enriched atmosphere diminished the phytotoxicity of neodymium in wheat (Triticum aestivum L.) - Saleh, Ahmed M.; Haridy, Maha S. A.; Mohammed, Afrah E.; Ziska, Lewis; Alotaibi, Modhi O.; Khalil, Ahmed M. A.; Madany, Mahmoud M. Y.; Abd Elgawad, Hamada; Amer, Hanaa E. A. (Frontiers in Plant Science, 2025)
IntroductionNeodymium (Nd), a rare earth element (REEs), is widely utilized in industry. Although the detailed biological role of Nd in plant biology is unclear, recent reports have noted its oxidative phytotoxicity at concentrations higher than 200 mg kg-1 soil. At present it is unclear if these detrimental effects could be offset by the global rise in atmospheric carbon dioxide concentration ([CO2]) which has been shown to enhance photosynthesis and growth in a wide range of C3 plant species. MethodsTo assess any amelioration effects of [CO2], a phytotoxic dose of Nd (III) was given to wheat grown under two scenarios of atmospheric CO2, ambient levels of CO2 (aCO2, 420 ppm) and eCO2 (620 ppm) to assess growth and photosynthesis.Results and discussionOur results suggest that at ambient [CO2], Nd treatment retarded wheat growth, photosynthesis and induced severe oxidative stress. In contrast, eCO2 reduced the accumulation of Nd in wheat tissues and mitigated its negative impact on biomass production and photosynthesis related parameters, i.e., photosynthetic rate, chlorophyll content, Rubisco activity and photochemical efficiency of PSII (Fv/Fm). Elevated [CO2] also supported the antioxidant defense system in Nd-treated wheat, enhanced production of enzymatic antioxidants, and more efficient ascorbate-glutathione recycling was noted. While additional data are needed, these initial results suggest that rising [CO2] could reduce Nd-induced oxidative stress in wheat.